Epilepsia Partialis Continua in a Patient with Progressive Multiple Sclerosis - Gökhan Görken; Abdullah Yılgör (Türk Nöroloji Dergisi, 2021)
Multiple sclerosis (MS) is a chronic autoimmune neurologic disease with demyelination. Epileptic seizures can be seen during episodes or out of the episodes in the course of MS. Although epileptic seizures are rare in patients with MS, they are more common than the normal population. We present a patient with MS who presented with epilepsia partialis continua, which could not be stopped with antiepileptics in the classic status epilepticus protocol but was limited with pulse steroid therapy.